Microscale Discrete Element Method Simulation of the Carbon Black Aggregate Fracture Behavior in a Simple Shear Flow. Issue 6 (14th January 2021) - Asylbekov, Ermek; Trunk, Robin; Krause, Mathias J.; Nirschl, Hermann
Abstract : The shear stress induced breaking behavior of carbon black (CB) aggregates during the manufacturing process of Li‐ion batteries is investigated via microscale discrete element method (DEM) simulations. The relevant range of shear stress is chosen according to a planetary mixer and cathode slurries with high solid content. Aggregates of different sizes and shapes are modeled using a self‐written algorithm based on the tunable dimension method. Then, suitable models are chosen for representing the solid bridges between the primary particles of the CB aggregates and relevant fluid forces. The results show a correlation between aggregate size and critical shear stress which is required to initiate aggregate fracturing. Furthermore, a change in aggregate shape is linked to applied stress and initial aggregate size and shape. Hence, a recommendation for an efficient disintegration of CB aggregates during the mixing process is made. Abstract : The breaking behavior of carbon black (CB) during the manufacturing of Li‐ion batteries is investigated on microscale using discrete element method (DEM) simulations. Based on this study, a link between occurring shear stress within a planetary mixer and resulting CB aggregate size and shape is presented. The results lead to a recommendation for an efficient dispersing process.